Anzac Day at Home and Abroad: Towards a History of Australia’s National Day - Scates, Bruce (History compass, 2012)
Over the last hundred years, Anzac Day (25 April), the anniversary of the initial landing of Australian and New Zealand Army Corps (ANZAC) at Gallipoli in 1915, has captured the Australian and New Zealand national imaginations. The day remembers the first significant engagement involving Australian and New Zealand soldiers in the First World War. This article is an early report of a major project that will chart Anzac Day’s origins, development and contested meanings. It is both an historical study, tracing changes in commemoration and remembrance over time, and an investigation of the ways in which Australians and New Zealanders mark Anzac Day in the present day. It will interrogate the shaping of historical sensibility by exploring the complex connections between personal and collective remembrance. One of the challenges to understanding Anzac Day is dealing with the multiplicity of meanings of such a large-scale, diverse and now venerable (in modern Australian terms) observation. It will also examine the neglected subject of Anzac Day’s observance outside the Australia and New Zealand - in Europe, Asia, North Africa and the Pacific - where it has long played a role in expressing the identities of Antipodean expatriate communities.